Does Banking Risk And Macroeconomics Variables Matter For Agricultural Sector? Evidence From Lampung Province - Ichsan Hamidi; Rasyida Pertiwi; Dirta Pratama Atiyatna; Abdul Bashir (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2023)
This research is conducted to investigate the factors that influence the financing of the agricultural sector on Islamic banking in Lampung Province. The data used in this research is time series data from Islamic Commercial Banks (BUS) and Islamic Business Units (UUS) in Lampung Province totaling 120 samples. The data are obtained from the statistical reports of the Financial Services Authority (OJK) on sharia banking in Indonesia, and data from the Indonesia Statistics (BPS). The method used is a quantitative analysis using multiple linear regression. This study shows that the variables of Financing to Deposit Ratio (FDR) and TPF have a positive and significant correlation. However, the SBIS variable has a negative and insignificant effect on Agricultural sector financing. On the other hand, the Non-Performing Financing (NPF) variable has a negative and significant correlation, and the variable Inflation has a positive and insignificant on the agricultural sector financing in Lampung province.